PERANCANGAN DAN PEMBUATAN DATABASE UNTUK PERUSAHAAN CRALOTS - Briyan Anggara Putra; Muhamad Raihan Nur; Opianus Lase (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Cralots Bakery Shop is a small business specializing in the production and sale of high- quality cakes and pastries. To enhance operational efficiency and improve customer service, Cralots Bakery Shop requires an integrated and effective database system. This research aims to design and implement a database that meets the needs of Cralots Bakery Shop. The initial stage involves an in-depth analysis of the shop's data requirements, including cake product data, raw material supplier data, customer data, inventory, and sales transaction data. In this database design, appropriate table structures and accurate table relationships will be established. Additionally, data security aspects will be considered to ensure the confidentiality of customer information and business data. The development method employed is an agile approach to ensure that the database implementation can adapt to the changing needs of Cralots Bakery Shop. The use of state-of-the-art database management systems (DBMS) is also emphasized in this research to ensure optimal performance and scalability. The outcome of this research is a successful and functional database implementation for Cralots Bakery Shop. This database allows the shop to manage inventory more effectively, optimize the ordering and delivery processes for raw materials, and enhance customer satisfaction through a loyalty system and purchase history records.